Nutrition, nutritional behavior, and obesity - Koleva, M; Kadiiska, A; Markovska, V; Nacheva, A; Boev, M (Central European journal of public health, 2000)
THE PURPOSE: Of this investigation is to explore the effect of several alimentary factors--such as diet, nutritional habits, and personal preferences--upon the occurrence of obesity. SUBJECTS: Of the study were 264 workers (203 men and 61 women) from the ammonium production department of a fertilizer plant, divided into two age groups: under 30 years and over 30 years. METHODS: The data are collected by means of a questionnaire about daily nutrition, including the types and average quantity of food (Food Frequency Questionnaires--FFQ). All collected information is analyzed by means of a computer program with a database that includes the chemical structure of food products and takes into account the losses in their nutritional value that occurs in the course of preservation and thermal processing. The nutritional status is assessed on the basis of a Body Mass Index (BMI): group I--normal body mass--BMI 18.5-25 kg/m2; group II--overweight--BMI 25.1-30 kg/m2; group III--obesity--BMI > 30 kg/m2. RESULTS: The assessment of the individual energy intake shows that hyper-energetic nutrition is typical for 67% of the individuals examined. There is no significant age and/or gender difference. This is the result of extra-intake of fat (over 30 E%), which is observed for 87.9% of all workers, and over 40 E% for almost half of the women examined. All age and gender groups display hyper-protein nutrition with pronounced cellulose (fiber) deficit, high daily intake of sodium, and disbalance of mineral salts as well as a relative deficit of vitamin A, B1, and PP. The frequency of overweight individuals is 43.9%, while that of obese individuals is 23.1%. The majority of workers (70.1% of group I, 63.2% of group II, and 79% of group III) have three meals a day. For 43% of group III individuals dinner is the largest meal. A significantly higher percentage of group III individuals (21.3%) think that they overeat. CONCLUSIONS: Hyper-energetic, disbalanced nutrition, and incorrect nutritional-behavioral model are factors that determine the prevalence of overweight and obesity among the workers examined.
Keywords: lidé středního věku; mladiství; Feeding Behavior; Male; dieta; dietní záznamy; dospělí; stravovací zvyklosti; hodnocení stavu výživy; obezita; lidé; Adolescent; ženské pohlaví; Nutrition Assessment; preference v jídle; Adult; Obesity; mužské pohlaví; Middle Aged; Diet; Humans; Diet Records; Body Mass Index; Food Preferences; index tělesné hmotnosti; Female